Microgeração de energia elétrica com gás de síntese de um gaseificador concorrente utilizando Itaúba mazilaurus - Chaves, Luiz Inácio (2012)
The use of biomass as energy source is one of the most promising, because it contributes to reduce emissions of carbon dioxide in the atmosphere and allow the decentralized energy generation. Gasification is a technology of processing biomass energy into a gaseous biofuel of low calorific value. The gas can be used in Otto cycle engine for power generation in isolated communities. This study evaluated the capacity of the gasification gas in a fixed bed gasifier downtraft of two stages, the wood consumption, the efficiency of the gasifier and the gas consumption and efficiency in apower-generator Otto cycle. The gasifier use was a TERMOQUIP brand, model CD 40. The evaluated power-generator was a BRANCO brand, direct injection and power of 13 cv coupled to an electric generator of 5.5 cv. The gasification gas was injected into the engine mixed with the intake air. The generator was subjected to loads ranging from 0.5 kW to 2.5 kW, with the aid of a bank of electrical resistances. The production of gas from the gasifier and gas consumption by the motor were measured by means of a gasometer. The average gas production resulting from the gasification of wood presented during testing was 14.28 m³ hˉ ¹. Wood consumption averaged 5.61 kg hˉ ¹. The average yield of gas per unit weight was approximately 2.55 m3kgˉ ¹. The gasification efficiency averaged 57.2%. When fed with synthesis gas, the output voltage of the generator was kept within the standards established by Companhia Paranaense de Energia (Copel, 2008), varying only between 221 and 223 V. For tests with the power-generator the best condition occurred for the highest load, 2.5 kW, where the gas consumption was about 10.6 m³ hˉ ¹ and specific fuel consumption of 4.8 m³ kWhˉ¹. For this condition, the average specific fuel consumption of equivalent wood was 1.9 kg kWh ˉ ¹ and the overall efficiency of power-generator was about 16.6%.